Highly thermally conductive and light responsive phase change cellulose film - kandil, Ivan; Fleming, Ian (Journal of Green Energy and Environmental Engineering, 2025)
Solar energy storage faces numerous challenges, which mainly stem from the intermittency of solar radiation and energy loss caused by uncontrolled spontaneous heat dissipation of conventional phase‑change materials (PCMs) under low‑temperature environments. On this basis, this study fabricated a novel light‑responsive phase‑change composite film (EC/mAZO/BNNs) via physical blending of ethyl cellulose (EC), 4‑methoxyazobenzene (mAZO) and boron nitride nanosheets (BNNs). Experimental results show that abundant hydroxyl groups in EC form strong hydrogen‑bond interactions with mAZO molecules. These interactions not only effectively inhibit premature crystallization of mAZO but also markedly stabilize its supercooled state, thereby achieving long‑term energy storage. Ultraviolet charging experiments demonstrate that the EC/mAZO/BNNs film reaches its photostationary state within 15 min, much faster than the 40 min required for pure mAZO, with greatly improved light‑response efficiency; its cis‑isomer content reaches 96.8 %, far higher than the 75.7 % of pure mAZO. When BNNs are doped at a mass fraction of 20 %, the thermal conductivity of the film rises to 0.74 W/(m·K), approximately ten times that of the EC/mAZO system without BNNs. In addition, this material can efficiently store light energy through dual mechanisms of isomerization enthalpy and phase‑change enthalpy, delivering an energy storage density of about 272.5 J/g. Practical application evaluations reveal that the film can rapidly conduct heat generated during the operation of electronic devices. It exhibits broad application prospects in the field of smart‑device thermal management and offers a feasible technical route for developing scalable, durable and multi‑functional solar‑thermal energy storage systems.